Deltheden hos Grundtvig efter 1832 - Elbek, Jørgen (Grundtvig-studier, 1975)
The Divided Mind of Grundtvig after 1832 By Jørgen Elbek This article is a concluding supplement to the little book, Grundtvig’s Eighteen Years of Apprenticeship, that is the years 1805-24, and is also concerned with an essay on the subsequent seven »lean« years, 1825-32. It was published in the periodical Kritik No. 31. According to Elbek, the rest of Grundtvig’s works are characterized by his recognition that he is of a mixed nature, which reveals itself in six main areas of his authorship:1. Grundtvig regards himself as a skald (»an ancient Scandinavian poet« - O.E.D.), standing by the hero’s side and dreaming of the glory the hero seeks to gain through his feats. Reference is made to the poem Til Kristne Venner (To Christian Friends) 1833, and to the poems written in memory of Poul Dons, Thorvaldsen and Kamma Rahbek (1843-45).2. Grundtvig regards himself as the historian of the people in his Universal History (Handbook of World History I-III, 1833-43), based on Joseph’s words to his brothers - » And as for you, you meant evil against me; but God meant it for good«. Genesis 50,20.3. Grundtvig works towards an education of young people that distinguishes between the knowledge which kills (like lightning) and that which is life-giving (like the sun). The aim of the High School teaching is not to convey all that we know, but only so much of it as can be common property to the benefit and pleasure of all. A social bond must be established between people who share the same language, not for example the same sort of work.4. It is a principal point o f Nordens Mytologi (Scandinavian Mythology) that people o f different faiths can work together if they just have the same spirit. And the spirit that pervades Scandinavia reveals itself in the old myths and always expresses itself as a battle tor immortality. This is what Grundtvig maintains, even though as a Christian he knows that immortality cannot be achieved by fighting. He can work together with »naturalists«.5. The Church is transformed from being the historical institution o f the Lord to being the place where He rises in the word here and now when the congregation are gathered.6. In the poems to his second wife Grundtvig sees himself as tne spirit and his wife as the heart. On the other hand, he asks her to take him totally, just as he takes her as she is. During his mental breakdowns in 1844 and 1867 he recognized that there was still much of the heathen in him.These main points are the result of a term’s courses at Aarhus Univ. on Grundtvig’s educational writings. They should be read as an answer to the review o f Elbek’s book in Grundtvig Studies 1974 p. 85-86.